The influence of advertisement boards, street and source layouts on CO dispersion and building intake fraction in three-dimensional urban-like models. (March 2019) - Lin, Yuanyuan; Chen, Guanwen; Chen, Taihan; Luo, Zhiwen; Yuan, Chao; Gao, Peng; Hang, Jian
Abstract: Heavy traffic flows commonly result in large vehicular pollutant exposure in near-road buildings. Street layouts and pollutant source settings are key factors. Advertisement boards are sometimes adopted for business purpose, but their impacts on pollutant dispersion and exposure are still unclear. Thus, this paper numerically investigates the influence of aspect ratios (building height/street width, H/Ws = 1 or 2; H = 30 m), source locations and advertisement-board settings on the flow, carbon monoxide (CO) dispersion and exposure within three-dimensional urban-like models under the parallel approaching wind to the main streets. Personal intake fraction ( P_iF ) represents the fraction of total vehicular emissions inhaled averagely by each person of a population. Spatial mean P_iF is named as < P_iF > and that for the entire building as building intake fraction (< P_iF >B ). With span-wise CO source fixed in target secondary streets of No 2 or 13 (S2 or S13), < P_iF > is particularly large in target streets. < P_iF >B decreases exponentially toward downstream from the target street and S13 cases attain greater < P_iF >B and larger exponential decreasing rates. Cases with H/Ws = 2 experiences more limited upward dispersion and subsequently smaller < P_iF > (0.155–0.339 ppm) of entire target street than cases with H/Ws = 1 (0.375–0.731 ppm). For cases with stream-wise CO source along the main street (Smain), < P_iF >B first rises quickly toward downstream, then adjusts to equilibrium values (0.051–0.063 ppm). Finally, with span-wise source, vertical and double-layer advertisement boards produce stronger upward CO transportation and greater < P_iF >B than lateral and single-layer types, while with Smain source, the double-layer and lateral types produce larger < P_iF >B and shorter exposure adjustment distance. Graphical abstract: Image 1 Highlights: With lateral CO source, < P_iF >B decreases exponentially toward downstream streets. With lateral source, < P_iF >T in entire target street is 0.2–0.7 ppm as H/Ws = 1–2. Vertical/double-layer advertisement boards get larger iF than lateral/single-layer. With stream-wise CO source, the equilibrium < P_iF >B is 0.05–0.06 ppm as H/Ws = 1–2. With stream-wise CO source, double-layer/lateral types get greater < P_iF >B.